Rapid homoploid hybrid speciation in British gardens: The origin of Oxford ragwort (Senecio squalidus). Issue 21 (26th September 2020) - Nevado, Bruno; Harris, Stephen A.; Beaumont, Mark A.; Hiscock, Simon J.
Abstract: Hybridisation can lead to homoploid hybrid speciation, i.e., the origin of new species without change in chromosome number between parents and offspring. Central to homoploid hybrid speciation is the role of hybridisation in the establishment of reproductive isolation between the hybrid and the parental species in the early stages of speciation, when typically all species occur at least partly in sympatry. In this work we analyse genome‐wide polymorphism data obtained by transcriptome sequencing of the British hybrid species Oxford ragwort ( Senecio squalidus, Asteraceae), its two Italian parental species ( S. aethnensis and S. chrysanthemifolius) and their naturally occurring hybrids on Mt Etna (Italy). We show that Oxford ragwort most likely originated from de novo hybridisation between its two Italian parental species whilst they were in cultivation in British gardens at the turn of the 18th century. Reproductive isolation between the new hybrid species and its parental species probably resulted from inheritance of genetic incompatibilities between the two parental species and subsequent ecological segregation – both of which have been shown in previous studies. Our results imply that S. squalidus meets the most stringent criteria set forth to identify homoploid hybrid speciation, and call attention to the creative role of hybridisation in responding to novel environmental conditions.